(3GdUGOM hGdHGZes - (3eMeO Hf eMeO Hf UGdM GdYHGSj, fXGe GdOjf CHh jYdj, GHf GdgHGQjI , J (B509 (3g` s
(3ChdgG (B:s
(3aHnJ aj CUd cfGSj aj GdNeQ hbO ScQJ HGddZhH hGdSeQ afeJ ddMjf LejY jhej Ke GfJHgJ aQbkG ef fhej s
(3BNQgG (B:s
(3Ef GdfahS GdaGFbI ddecQeGJ YGTbI bGdJ dgG GdNWHGA GMSfJ jG MSfGA s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdfSNI HgG MhGTs
(3fSNI JGSYIs
(3bWYI efgs
(3hHgGeTgG YfhGfGJ ehVhYGJgG s
(3JHUQI GdYfhGf (B:s
(3fXe s
Keywords: (3GdCOHs